The Heroic Theft: Myths from Rgveda IV and the Ancient Near East - Knipe, David M.
340 ff.: Etana- und Zû-Mythus, auch in Darstellungen der Kleinglyptik; 351-355: The Cosmic Tree and Reintegration; 355-358: The Magic Plant; 358-360: The Guardian’s Price.